Ranquilite, a calcium uranyl silicate - Jiménez de Abeledo, María E.; Rodríguez de Benyacar, María A.; Galloni, Ernesto E. (1960)
Fil: Jiménez de Abeledo, María E. Comisión Nacional de Energía Atómica; Argentina